Utilization of Java Acid Seed (Tamarindus indica) Extract as a Coagulant in Tofu Waste Treatment Process: Short Communication - Meri Letik; Luther Kadang; Suwari (Journal of Applied Chemical Science, 2013)
A study concerning the utilization of java acid seed (tamarindus indica) extract as a coagulant to be developed further for tofu wastewater treatment has been conducted. This study aimed to determine the optimum concentration of tamarind seed coagulant and to know the ability of the coagulant to reduce the concentration of total solid suspended (TSS), biochemical oxygen demand (BOD), chemical oxygen demand (COD) and amonia at optimum pH and temperature. In this study, jar-test method was used to confirm the effective dose of tamarind seed extract in reducing turbidity of the water samples analyzed. The applied concentrations of the seed extracts were 2000, 4000 and 6000 ppm. The results showed that the optimum dosage to reduce TSS, BOD and ammonia was 2000 mg/L and the COD was 4000 mg/L . At the optimum concentrations, the coagulant ameliorated up to 92.92% of BOD, 91.30% of COD, 83.34% of TSS, and 97.46% of ammonia levels and the water treated was found visually clear. Those results conclusively indicates that the coagulant made from the tamarind seed ameliorates effectively the BOD, COD, TSS, and ammonia contents as well as the turbidity levels of the water samples flowing from the tofu industry.